2014
DOI: 10.1007/s11295-014-0739-8
|View full text |Cite
|
Sign up to set email alerts
|

High genetic similarity between Polish and North European Scots pine (Pinus sylvestris L.) populations at nuclear gene loci

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. Polish populations share the same genetic background at the analysed nuclear gene markers.However, the populations showed a much closer genetic relationship with North European samples than other regional groups of populations. Across the very uniform genetic background of the populations we identified several gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
3
14
1
Order By: Relevance
“…Both geographical regions had similar allelic frequency spectra distributions, and no significant correlation between genetic differentiation and geographical distance between populations was found for the nuclear and chloroplast loci in the Mantel test. Obtained results are in accordance with other studies on P. sylvestris in the continuous species distribution in Europe using isoenzymes and DNA markers (Dvornyk et al 2002;Garcia-Gil et al 2003;Goncharenko et al 1994;Pyhäjärvi et al 2007;Wachowiak et al 2014;Wang et al 1991). Considering the large geographical areas covered by investigated populations, it seems that their genetic similarity must result from shared phylogeographic history.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both geographical regions had similar allelic frequency spectra distributions, and no significant correlation between genetic differentiation and geographical distance between populations was found for the nuclear and chloroplast loci in the Mantel test. Obtained results are in accordance with other studies on P. sylvestris in the continuous species distribution in Europe using isoenzymes and DNA markers (Dvornyk et al 2002;Garcia-Gil et al 2003;Goncharenko et al 1994;Pyhäjärvi et al 2007;Wachowiak et al 2014;Wang et al 1991). Considering the large geographical areas covered by investigated populations, it seems that their genetic similarity must result from shared phylogeographic history.…”
Section: Discussionsupporting
confidence: 90%
“…Populations from a broad pine distribution showed a high level of genetic variation and a low level of among-population genetic differentiation (Belletti et al 2012;Prus-Glowacki et al 2003;Pyhäjärvi et al 2007;Wachowiak et al 2014;Wang et al 1991). This low genetic structure in a wide distribution of Scots pine is typical for geographically core populations and among others, it results from high outcrossing and random mating in pines (Petit and Hampe 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches for resolving the genetic architecture of adaptive traits in species derived from heterogeneous environments such as the taxa from the P. mugo complex should take into account the high within‐population variation of the studied traits. Comparison of genetic variation between populations could be effective in species like P. sylvestris which exhibit strong clines in adaptive traits, assuming that they represent populations of shared evolutionary and demographic history (Wachowiak et al ). The study demonstrates genetically driven variation in pine phenotypes across the species distribution in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of genetic variation between populations could be effective in species like P. sylvestris which exhibit strong clines in adaptive traits, assuming that they represent populations of shared evolutionary and demographic history (Wachowiak et al 2014). The study demonstrates genetically driven variation in pine phenotypes across the species distribution in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation may evolve from new mutations, standing genetic variation or introgression. Kane & Rieseberg, 2007;Rieseberg et al, 2007;de Carvalho et al, 2010;Lexer et al, 2010;Scascitelli et al, 2010;Chen et al, 2012;Muir et al, 2013;Wachowiak et al, 2014b Senecio detrimental in another (Mitchell-Olds et al, 2007). In a close relative of A. thaliana, the US subspecies of A. lyrata, Turner et al (2010) found candidate loci for serpentine adaptation, using A. thaliana homologs as a reference.…”
Section: Arabis Alpinamentioning
confidence: 99%